EFFECTS OF PARTICLE SIZE AND TYPE OF AMMONIATION-PRESERVATION ON THE DIGESTIBILITY AND INTAKE OF CORN CROP RESIDUES IN SHEEP - Jiménez A., Ronald (2010)
The effect of particle size (PS) and type of ammoniation-preservation (AP) on the digestibility and intake of corn crop residues in sheep was evaluated. Four sheep were used in a 4 x 4 factorial arrangement: PS (1, 2, 3, and 4 cm) and AP [no ammoniated no silage (NA) and three ammoniated treatments with different plastic silage: aerial silage on the soil (AS), silage on the soil covered with ground (SC) and silage interred in a compost pit (SI)]. There was no effect of PS, but ammoniated silage treatments (AS, SC, SI) significantly (p<0.01) improved the digestibility and intake of the corn crop residue. AS and SI performed better in protein and fiber digestibility. It was concluded that the 2 cm-AS combination was considered the most appropriate from an economic, practical and technical viewpoint.